2012
DOI: 10.3189/2012jog10j218
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of supercooling: McMurdo Sound platelet ice

Abstract: ABSTRACT. Near ice shelves around Antarctica the ocean becomes supercooled and has been observed to carry small suspended ice crystals. Our measurements demonstrate that these small crystals are persistently present in the water column beneath the winter fast ice, and when incorporated in sea ice they reduce the mean grain size of the sea-ice cover. By midwinter, larger ice crystals below the ice/water interface are observed to form a porous sub-ice platelet layer with an ice volume fraction of 0.25 ± 0.06. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
189
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(212 citation statements)
references
References 49 publications
22
189
1
Order By: Relevance
“…The ISW plume is the second mechanism. The influence of this plume on sea ice processes has been documented in studies of sea ice structure and growth Dempsey et al, 2010;Mahoney et al, 2011;Gough et al, 2012). Satellite altimeter observations have indicated that the locations of the largest increases in multiyear sea ice thickness from 2003-2009 during the NASA ICESat mission (Price et al, 2013) were coincident with the greatest abundance of platelet ice (Dempsey et al, 2010).…”
Section: Maps Of Sea Ice and Snow Cover Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations
“…The ISW plume is the second mechanism. The influence of this plume on sea ice processes has been documented in studies of sea ice structure and growth Dempsey et al, 2010;Mahoney et al, 2011;Gough et al, 2012). Satellite altimeter observations have indicated that the locations of the largest increases in multiyear sea ice thickness from 2003-2009 during the NASA ICESat mission (Price et al, 2013) were coincident with the greatest abundance of platelet ice (Dempsey et al, 2010).…”
Section: Maps Of Sea Ice and Snow Cover Characteristicsmentioning
confidence: 97%
“…Using this method in McMurdo Sound, Gough et al (2012) report ρ i as 934 kg m −3 . Using an amended method at seven of our measurement sites in 2011 (where ρ i estimate for each site is the mean of ρ i derived from five drill-hole measurements -see Fig.…”
Section: Estimating Solid Fraction Under the Hydrostatic Equilibrium mentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate SIPL thickness at the n th time interval, we adopt the assumptions of HU14 that solid ice fraction within 15 the SIPL is 0.25 (Gough et al, 2012) and that the ice crystals double in volume after precipitation:…”
Section: Isw Model In Mmsmentioning
confidence: 99%